2014
DOI: 10.1186/s12870-014-0236-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide annotation of the soybean WRKY family and functional characterization of genes involved in response to Phakopsora pachyrhiziinfection

Abstract: BackgroundMany previous studies have shown that soybean WRKY transcription factors are involved in the plant response to biotic and abiotic stresses. Phakopsora pachyrhizi is the causal agent of Asian Soybean Rust, one of the most important soybean diseases. There are evidences that WRKYs are involved in the resistance of some soybean genotypes against that fungus. The number of WRKY genes already annotated in soybean genome was underrepresented. In the present study, a genome-wide annotation of the soybean WR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 80 publications
5
51
1
Order By: Relevance
“…Additional phylogenetic analyses, however, have shown that the group II proteins can be further divided into groups IIa–e ( Zhang and Wang, 2005 ). Through extensive searching and sequence verification with the annotated soybean genome, we identified more than 170 WRKY genes from soybean, which is significantly more than the 133 members identified from a previously reported study with BLAST searching used Arabidopsis WRKY proteins as queries ( Yin et al , 2013 ), but similar to the number identified from a more recent study through genome-wide annotation ( Bencke-Malato et al , 2014 ). Phylogenetic analysis through multiple sequence alignment of the WRKY domains classifies the vast majority of soybean WRKY proteins into one of the seven groups.…”
Section: Resultsmentioning
confidence: 70%
“…Additional phylogenetic analyses, however, have shown that the group II proteins can be further divided into groups IIa–e ( Zhang and Wang, 2005 ). Through extensive searching and sequence verification with the annotated soybean genome, we identified more than 170 WRKY genes from soybean, which is significantly more than the 133 members identified from a previously reported study with BLAST searching used Arabidopsis WRKY proteins as queries ( Yin et al , 2013 ), but similar to the number identified from a more recent study through genome-wide annotation ( Bencke-Malato et al , 2014 ). Phylogenetic analysis through multiple sequence alignment of the WRKY domains classifies the vast majority of soybean WRKY proteins into one of the seven groups.…”
Section: Resultsmentioning
confidence: 70%
“…WRKY transcription factors have been identified as one the largest families of regulatory proteins, and there is increasing evidence indicating that WRKYs are involved in soybean defense responses to pathogens 35 and soybean aphids 36 . In our study, we identified 83 WRKY genes that were expressed in S54 roots based on available annotations (Table S13 ), 33 (39.8%) of which were significantly induced after H. glycines infection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were observed in other species, where it was concluded that stomatal aperture was the main factor limiting leaf photosynthetic capacity in NaCl-treated plants (Loreto et al, 2003; Meloni et al, 2003). The lack of alterations in PSII functionality under salt stress might be the result of an increase in photoprotection mechanisms, such as Non-Photochemical Quenching and cyclic electron flow (Bencke-Malato et al, 2014; Dionisio-Sese and Tobita, 2000), or the increase in the activity of ROS scavenging mechanisms in the chloroplast (Badawi et al, 2004; Meloni et al, 2003). The latter was previously reported to take place in other Lotus species, although under low temperature conditions (Calzadilla et al, 2016).…”
Section: Discussionmentioning
confidence: 99%